1Department Of Complexity Science and Engineering,Devision Of Trans Disciplinary Science,University Of Tokyo, JAPAN. - Adharvanachary, M (International Journal of Pharmaceutical & Biological Archive, 2011)
ABSTRACTAbstract: Some Hitherto unknown complexes of Alloxan Thiosemicarbazone and Substituted Thiosemicarbazones with Au(III) have been synthesized and characterized by elemental Analysis,spectral viz. FT-IR,NMR,UV-Vis,Mass etc, magnetic, thermal and conductance studies.All complexes are crystalline powders decomposed by mineral acids.the spectral and other data indicate that all the Au(III) complexes are tetrahedral.The ligand,its Schiff’s Bases and and metal chelates would be screened in-vitro for anticancer activity against some cancer Cell lines.